2019
DOI: 10.1016/j.electacta.2019.03.194
|View full text |Cite
|
Sign up to set email alerts
|

Self-stratified and self-powered micro-supercapacitor integrated into a microbial fuel cell operating in human urine

Abstract: A self-stratified microbial fuel cell fed with human urine with a total internal volume of 0.55 ml was investigated as an internal supercapacitor, for the first time. The internal self-stratification allowed the development of two zones within the cell volume. The oxidation reaction occurred on the bottom electrode (anode) and the reduction reaction on the top electrode (cathode). The electrodes were discharged galvanostatically at different currents and the two electrodes were able to recover their initial vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 110 publications
(155 reference statements)
3
22
0
Order By: Relevance
“…[60] Simple carbonaceous-based materials used in this work as electrodes for MFCs were shown previously to display supercapacitive features and enhance power output. [63][64][65][66] In this study, the peak in power curves showed during the polarization curve was 0.56 mW while the peak in power determined during galvanostatic discharge was 1.4 mW (at i pulse of 4 mA over 1 s) which was 2.5 times higher despite operated intermittently. The supercapacitive operation, therefore, present benefits compared to the continuous operation.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…[60] Simple carbonaceous-based materials used in this work as electrodes for MFCs were shown previously to display supercapacitive features and enhance power output. [63][64][65][66] In this study, the peak in power curves showed during the polarization curve was 0.56 mW while the peak in power determined during galvanostatic discharge was 1.4 mW (at i pulse of 4 mA over 1 s) which was 2.5 times higher despite operated intermittently. The supercapacitive operation, therefore, present benefits compared to the continuous operation.…”
Section: Discussionmentioning
confidence: 46%
“…The MFCs operation mode in intermittent and supercapacitive mode introduced recently in 2016 explores the galvanostatic discharges of the MFC electrodes considered like an internal supercapacitor . Simple carbonaceous‐based materials used in this work as electrodes for MFCs were shown previously to display supercapacitive features and enhance power output . In this study, the peak in power curves showed during the polarization curve was 0.56 mW while the peak in power determined during galvanostatic discharge was 1.4 mW (at i pulse of 4 mA over 1 s) which was 2.5 times higher despite operated intermittently.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…A single cascade of 6 modules electrically connected in series produced a continuous electrical output of 2.5 V at 40 mA (100 mW), and was able to power 3 h of continuous phone communication every 6 h, with as little as 600 mL urine every 6 h. [70] Beside urine treatment and power generation, this type of design was also applied to the development of internal selfpowered supercapacitive MFCs fed with human urine. [73] Supercapacitor MFCs (empty volume 550 μL) were shown to produce a peak power of � 1.20 mW ( � 2.19 mW ml À 1 ) for a pulse time of 0.01 s that decreased to � 0.65 mW ( � 1.18 mW ml À 1 ) for longer pulse periods (5 s). Moreover, these microbial supercapacitors demonstrated relatively stable operation over 44 h with � 2600 recharge/discharge cycles.…”
Section: Membraneless Microbial Fuel Cell Treating Urinementioning
confidence: 99%
“…Beside urine treatment and power generation, this type of design was also applied to the development of internal self‐powered supercapacitive MFCs fed with human urine . Supercapacitor MFCs (empty volume 550 μL) were shown to produce a peak power of ≈1.20 mW (≈2.19 mW ml −1 ) for a pulse time of 0.01 s that decreased to ≈0.65 mW (≈1.18 mW ml −1 ) for longer pulse periods (5 s).…”
Section: Bioelectrochemical Systems Fed With Urinementioning
confidence: 99%